Innovative Al6061-gadolinium oxide ods alloys: fabrication and comprehensive characterization of microstructural, physical, mechanical, and radiation shielding properties - Almisned, Ghada; Yayla, Nihal; Albayrak, Muhammet Gokhan; Guler, Omer; Baykal, Duygu Sen; Tekin, H. O. (Springer Heidelberg, 2024)
This study explores the development and comprehensive characterization of Al6061-Gd2O3 composites, designed to enhance radiation shielding and mechanical properties for critical applications in environments exposed to ionizing radiation. The purpose of this research is to assess the effectiveness of Gd2O3 as a reinforcing material for Al6061, with the aim of creating a dual-function composite that combines structural integrity with superior gamma-ray and neutron attenuation capabilities. Using X-ray diffraction (XRD) and scanning electron microscopy (SEM), we analyzed the microstructural effects of varying Gd2O3 content, observing homogeneous dispersion at low concentrations and clustering at higher levels. Mechanical properties demonstrated that increased Gd2O3 content reduces the elastic modulus, indicating a trade-off between stiffness and shielding efficiency. Radiation shielding parameters, including Transmission Factor (TF), mass attenuation coefficient (MAC), and Fast Neutron Removal Cross Section (FNRCS), were evaluated through Phy-X/PSD and PHITS Monte Carlo simulations. Results indicate that Gd2O3 reinforcement significantly improves gamma-ray and neutron shielding, particularly at higher concentrations, making the composite viable for non-structural applications prioritizing radiation protection. The findings from this study highlight the potential of Gd2O3-reinforced Al6061 composites to serve as effective shielding materials in environments where radiation exposure is a primary concern.
Keywords: Al6061; Gd2O3; XRD; SEM; Alloys; Shielding